‘On the Rag’: Consumer behaviours towards menstrual products, and attitudes towards reusable menstrual products. - Canton-Lamousse, Clara (2020)
The study is based in the field of consumer behaviour research in marketing and explores the circumstances and factors through which different menstrual products are selected for consumption. This dissertation exposes the health and environmental dangers of single- use disposable products and aims to understand why the market is dominated by them instead of reusable menstrual products, which are the healthier and more sustainable alternative. Through the combination of theoretical and empirical qualitative research, the study explores why women have normalised the use of single-use disposable menstrual products, what their motivations for consuming certain menstrual products are, and what are their attitudes towards reusable menstrual products. Cultural practices, such as menstruation, are related to broader systems of power functioning through social phenomena such as class, gender, ethnicity etc. In this study, menstrual product choices and attitudes are articulated through social and political discourses using an ecofeminist approach. I decided to do research in this topic to explore possible motivations that could inform marketing strategies to increase the adoption of reusable menstrual products in the UK market. Twelve in-depth interviews were carried out with young women from the UK and the interviews were coded using a thematic analysis. The findings highlight the importance of practicality and comfort in a menstrual product and present social stigma as a barrier in the adoption of reusable menstrual products. The study demonstrates the political power that menstrual products hold as they represent dominant narratives of gender identity inscribed on the female body.